The relationship between self-concept and communication skills towards academic achievement among secondary school students in Johor Bahru - Yahaya, Azizi (Canada Center of Science and Education, 2009)

(untitled)
The article reviews empirical studies which emphasize that the relationship of self-concept and interpersonal communication skills to academic achievement. 320 students from eight schools in Johor Bahru were picked at random using the simple random method. The assessment instruments used in this study were the “Tennessee Self??Concept Scale” (TCS) and “Interpersonal Communication Skills Inventory” (ICSI). The reliability level of the assessment instruments is 0.7498 (TSCS) and 0.7587 from the pilot study done on a group of twenty respondents. The data was analyzed using the Pearson’s correlation and descriptive statistics. The students’ levels of dimension of self-concept (physical, personal, moral and ethic, behavior, social satisfaction and identity) and interpersonal communication skills were identified. The students’ PMR examination results were used as the academic achievement indicator. The results indicated that the majority of the students possessed the moderate level of self-concept and interpersonal communication skills. Self-concept was found to correlate quite significantly with interpersonal communication skills but it was found that self-concept does not correlate significantly with academic achievement. Suggestions were put to improve the students’ interpersonal communication skills and their self-concept. One of the suggestions is that communication skills should be introduced as a subject in the school curriculum from the primary level. This will not only develop a student’s self-confidence but also enhance his self-concept.